An Enhanced Distribution Transforming Encoder (Dte) Of The Honey Encryption Scheme For Reinforcing Text-Based Encryption - Omolara, Abiodun Esther (2020)
Honey Encryption (HE) is a cryptosystem used as a reinforcement to the conventional encryption scheme to address brute-force attacks specifically in the context of password-based encryption systems. The HE scheme relies on a model called the Distribution Transforming Encoder (DTE), which focuses on the use of deception as a key defensive approach in the design of primitives that facilitate information security by yielding plausible-looking but fake plaintext during decryption using an incorrect key.